(untitled) (Raparin Journal of Humanities (RJH), 2021)
This study deals with the colonial perspectives in Dave Eggers’s A Hologram for The King (2012), according to the postcolonial approach. Although colonialism era is over by now, colonial perspectives remain strong in some literary works. Since its advent in the second half of the twentieth century, postcolonial theory confronts colonial attitudes and experiences as colonialism has been justified in many works of Western writers and scholars who have distorted the real image of non-Europeans and non-Westerners via different means and techniques in masquerade of orientalism. Postcolonial discourse opposes the misrepresentation of non-Europeans and argues that such falsification is driven by political, social, religious and economic motives. In the current study, the researcher aims at explaining the notions of colonialism, otherization and other falsified images of non-Westerners in A Hologram for the King. This paper mainly questions Eggers’s portrayal of the protagonist, Alan Clay, who after bankruptcy and failure at home, flies to Saudi Arabia and capitalizes on the physical and moral assets of the Orientals in this country to convert his story of failure to a success. The characterization of the oriental world and its setting show Eggers’s being biased against the Eastern world and ironically mirror clear hints of colonialism and eurocentrism.